2017
DOI: 10.5152/tjbh.2016.3136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clinical Pilates Exercises on Patients Developing Lymphedema after Breast Cancer Treatment: A Randomized Clinical Trial

Abstract: Objective: The aim of the present study was to compare the effects of clinical Pilates exercises with those of the standard lymphedema exercises on lymphedema developing after breast cancer treatment. Materials and Methods:The study comprised 60 female patients with a mean age of 53.2±7.7 years who developed lymphedema after having breast cancer treatment. The patients were randomized into two groups: the clinical Pilates exercise group (n=30), and the control group (n=30). Before, and at the 8th week of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 37 publications
1
43
0
4
Order By: Relevance
“…22 Step 2: Of the 26 articles, 10 directly reported the outcome measures selected for the meta-analyses. Four studies [23][24][25][26] were utilized for absolute volume, four studies 14,24,27,28 for relative volume, and five studies 21,24,27,29,30 for the DASH (►Table 1). Statistics were assessed using standard mean difference and were analyzed using SAS software.…”
Section: Phase 4: Statistical Analysismentioning
confidence: 99%
“…22 Step 2: Of the 26 articles, 10 directly reported the outcome measures selected for the meta-analyses. Four studies [23][24][25][26] were utilized for absolute volume, four studies 14,24,27,28 for relative volume, and five studies 21,24,27,29,30 for the DASH (►Table 1). Statistics were assessed using standard mean difference and were analyzed using SAS software.…”
Section: Phase 4: Statistical Analysismentioning
confidence: 99%
“…A great deal of research [2][3][4][5] indicates that women, who undergoing breast surgery, axillary radiotherapy, chemotherapy are more likely to have higher risk of breast cancer-related lymphedema and impaired shoulder range of motion. The importance of the problem is underlined by the presence of numerous surgical methods 2 and conservative therapies 6,9,11,12 for overcoming upper extremity disorders in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The majority of women are treated with a wide variety of methods that have steadily improved their outcomes. Many reports showed the effectiveness of acupuncture, 9 lymphatic drainage, 10 Pilates-based exercises, [11][12][13] Yoga exercises, 14,15 Nordic Walking 16 for treatment and postoperative prevention breast cancer-related lymphedema, improvement quality of life of woman.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that different types of physical activity may be an effective method of attenuating the depression, anxiety, and fatigue in breast cancer survivors [21][22][23]. At the same time, it is emphasized that the rehabilitation program should be individualized for all breast cancer patients in accordance with their age, functional state, and physical activity level.…”
Section: Discussionmentioning
confidence: 99%